Digital (Crypto-Based) Capital Markets for Financial Inclusion: Security Tokens and Infrastructure - Habib Ahmed; Nida Khan; Habib Ahmed; Nida Khan (Bank Indonesia, 2026)
While small and medium enterprises (SMEs) play an important role in the economy, they face huge impediments to raising capital. Financial institutions are generally not eager to lend to SMEs for various reasons, and capital markets involve complex processes and infrastructure, which inhibit small firms from raising capital. While most research on cryptoassets focuses on cryptocurrencies, this paper examines how security tokens can enhance financial inclusion and presents a framework for enabling digital, crypto-based capital markets. The use of digital technology and the issuance of security tokens significantly reduce transaction costs, enabling SMEs to raise funds and providing opportunities to investors to invest in alternative asset classes. This study identifies the frameworks and features of cryptoassets and exchanges that SMEs can use to raise capital, as well as the issues that must be addressed in doing so. Specifically, the paper discusses issues related to the issuance, listing, trade, and post-trade mechanisms in digital exchanges. The use of Shariah-compliant equity- and assetbased security tokens to raise capital through digital capital markets can play an important role in enhancing financial inclusion and promoting development in Organisation of Islamic Cooperation member countries.